2015
DOI: 10.1007/s00374-015-1046-8
|View full text |Cite
|
Sign up to set email alerts
|

The molecular characteristics of compost affect plant growth, arbuscular mycorrhizal fungi, and soil microbial community composition

Abstract: Compost amendment to agricultural soils influences plant growth and soil quality by affecting activity of arbuscular mycorrhizal fungi (AMF) and composition of microbial community. We related the molecular composition of compost of different maturity added to soils to their effects on maize growth, N and P uptake, AMF root colonization and growth, and composition of soil microbial community. The characteristics of compost after different days of maturation (C60, C90, C120) were provided by 13 C-solid state NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 79 publications
5
53
0
4
Order By: Relevance
“…Compost amendment increases soil organic matter content, water holding capacity, and nutrients (Termorshuizen et al ). In addition, compost addition stimulates soil microbial communities (Carlson et al ; Cozzolino et al ). Compost application to severely degraded landscapes has been shown to increase grassland plant survivorship and primary production (Noyd et al ; Kohler et al ; Gil‐Loaiza et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Compost amendment increases soil organic matter content, water holding capacity, and nutrients (Termorshuizen et al ). In addition, compost addition stimulates soil microbial communities (Carlson et al ; Cozzolino et al ). Compost application to severely degraded landscapes has been shown to increase grassland plant survivorship and primary production (Noyd et al ; Kohler et al ; Gil‐Loaiza et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Different soils contain a great diversity of fungal species, whose spatial distribution results from many factors, such as plant diversity, soil properties, land use and dispersal, and climate [4,5]. Soil fungal community structures, in turn, directly affect the properties and fertility of soil, thereby influencing the growth of plants; the soil microbial population and abundance is thus positively correlated with soil fertility and plant growth status [6][7][8]. Hence, it has practical significance to investigate the distribution characteristics of soil microbiota, in which fungi take up an important position.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the microbial community structure was changed in ZL relative to the other treatments, throughout the time of sampling. Cozzolino et al, (2016) and Tejada et al, (2006) reported that the chemical properties of compost used as an amendment may affect the microbial community structure of soil.…”
Section: Extracellular Enzymatic Activity (Eea) Representsmentioning
confidence: 99%